2010
DOI: 10.1002/ibd.21178
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced expression of proproliferative and antiapoptotic genes in ulcerative colitis-associated neoplasia

Abstract: These results suggest that telomerase and ILK activation occurs during the later stages of carcinoma progression, whereas upregulation of survivin, c-MYB, and Tcf-4 is a feature of the early stage of development of neoplasia, and thus, they might serve as early indicators for UC-associated colorectal carcinogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 34 publications
1
5
0
Order By: Relevance
“…These proteins are involved in cell cycle regulation, proliferation, and apoptosis. As there is increased cell turnover in UC associated with neoplastic transformation and transfection of miR-143 and miR-145 inhibits proliferation in transfected cells, these cell cycle and cell death regulators were of interest to study in high-risk individuals (11, 23, 30–32, 42). This is the first study in ulcerative colitis to determine expression levels of these proteins that have potential roles in inflammation-associated neoplastic transformation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These proteins are involved in cell cycle regulation, proliferation, and apoptosis. As there is increased cell turnover in UC associated with neoplastic transformation and transfection of miR-143 and miR-145 inhibits proliferation in transfected cells, these cell cycle and cell death regulators were of interest to study in high-risk individuals (11, 23, 30–32, 42). This is the first study in ulcerative colitis to determine expression levels of these proteins that have potential roles in inflammation-associated neoplastic transformation.…”
Section: Discussionmentioning
confidence: 99%
“…With chronic inflammation, the epithelium undergoes recurrent injury and healing that is thought to predispose to the risk of malignant transformation (6, 7). Molecular and genetic changes accompany this transformation and may occur before there is histological evidence of dysplasia (6, 811). In this regard, several previous studies have reported differences in colonic mucosal gene expression in IBD patients compared to normal controls (1215).…”
Section: Introductionmentioning
confidence: 99%
“…It is known that iNOS/nitric oxide plays an integral role during intestinal inflammation, and the expression of iNOS was significantly increased in inflamed colon [42,43]. However, whether iNOS is induced in the hindgut in HFD mediated obesity mice is still unclear.…”
Section: Accepted Manuscriptmentioning
confidence: 97%
“…N-acetylcysteine inhibited chronic ulcerative colitis-associated colorectal adenocarcinoma development, possibly by reduction of nitrative DNA damage produced via iNOS in a murine model (Seril et al, 2002). Moreover, the expression of iNOS mRNA was significantly increased during neoplastic transformation of colonic mucosa in ulcerative colitis patients (Svec, et al, 2010). These data implicate that iNOS/NO plays a role in inflammation-associated carcinogenesis of the gut.…”
Section: Introductionmentioning
confidence: 72%